2019
DOI: 10.21203/rs.2.15946/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of ThSOS from Tamarix hispida improves salt tolerance

Abstract: Highlights ● The functional characterization of ThSOS genes were investigated by bioinformatics analysis and molecular characterization. ● ThSOS genes can respond to abiotic stresses (salt and drought) and hormone treatment (ABA). ● ThSOS3 gene overexpression increased ROS-scavenging capability and decreasing lipid peroxidation in cell membrane. ● ThSOS3 could effectively enhance the tolerance of transgenic T. hispida and Arabidopsis to salt stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The amount of ethylene released from seedling cotyledons after low temperature stress can be used as an identi cation index of cold tolerance of cucumber, and there is a positive correlation between cold tolerance and ethylene release of cucumber varieties (Liu et al, 1994). Previous studies have shown that under low-temperature stress, AnGolS1 overexpression can not only enhance the low temperature resistance of tomato plants, but also enhance the expression of genes related to ethylene (ET) signal transduction, such as one ACC synthase (ACS1) and ve ACC oxidase (ACO) up-regulated signi cantly (Liu, 2019). Present study shows that mepiquat chloride could increase the expression level of key enzyme genes LcACS in ethylene biosynthesis pathway, and promote the expression of EIN gene in ethylene signal transduction pathway, thus promoting ethylene signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of ethylene released from seedling cotyledons after low temperature stress can be used as an identi cation index of cold tolerance of cucumber, and there is a positive correlation between cold tolerance and ethylene release of cucumber varieties (Liu et al, 1994). Previous studies have shown that under low-temperature stress, AnGolS1 overexpression can not only enhance the low temperature resistance of tomato plants, but also enhance the expression of genes related to ethylene (ET) signal transduction, such as one ACC synthase (ACS1) and ve ACC oxidase (ACO) up-regulated signi cantly (Liu, 2019). Present study shows that mepiquat chloride could increase the expression level of key enzyme genes LcACS in ethylene biosynthesis pathway, and promote the expression of EIN gene in ethylene signal transduction pathway, thus promoting ethylene signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%